PWE-013 Evaluation of Faecal Aspirate as a Proxy for Colonoscopy Biopsy Sampling to Assess Microbial Diversity. (4th June 2013) - Watt, E; Berry, S; Farquarson, F; Glaire, M; Thomson, J; El-Omar, E; Louis, P; Hold, G
Abstract : Introduction: The gut microbiota plays a key role in Inflammatory Bowel Disease (IBD) pathogenesis and is also involved in colorectal neoplastic progression. In particular, the "dysbiosis" theory has evolved from work which has shown IBD sufferers to have different microbiologic profiles to normal controls. There is strong evidence to demonstrate that individuals harbour a unique microbiota with faecal and mucosal ecosystems being distinct. This would indicate that faecal samples are not appropriate surrogate markers for mucosal samples and other alternative sampling options should be considered. The aim of the study was to assess the microbial diversity of paired biopsies and faecal aspirates to determine whether faecal aspirate can be used as a suitable surrogate for colonic biopsies. Methods: Bacterial DNA was extracted from 21 paired mucosal biopsies and faecal aspirates, and subjected to denaturing gradient gel electrophoresis (DGGE) and q-PCR analysis to quantify the relative abundance of the following major bacterial groups: Bacteroidetes, Ruminococcaceae, Lachnospiraceae and Enterobacteriaceae . The relative abundance of bacterial groups was expressed as a percentage of total bacteria. Results: Increased variation was found across the faecal aspirates compared to biopsies with regards to relative abundance of the four bacterial groups analysed by q-PCR (Table 1). This indicates that microbial diversity of faecal aspirates is more variable than mucosal biopsies. When the mean abundance of each bacterial group across the biopsies and across the faecal aspirates was compared using a Paired t-test, there was a significant difference in levels of Bacteroides (62.3% vs 44.4%; p = < 0.05) but not the other bacterial groups. There was no statistical correlation between paired faecal aspirate and biopsy samples when analysed for the four major bacterial groups by linear regression. Conclusion: Substantial microbial diversity differences exist between faecal aspirate and biopsy samples. Faecal aspirates demonstrate considerably more variation than biopsies, and there would appear to be no correlation between paired samples. These results suggest that faecal aspirate is not a suitable microbiological surrogate for mucosal biopsies. Disclosure of Interest: None Declared.